Nosocomial Infections During Extracorporeal Membrane Oxygenation in Pediatric Patients: A Multicenter Retrospective Study - Wang, Chunle; Li, Shuanglei; Wang, Feng; Yang, Jinfu; Yan, Wei; Gao, Xue; Wen, Zhiqiang; Xiong, Yaoyao (Frontiers in Pediatrics, 2022)
Objective Extracorporeal membrane oxygenation (ECMO) is increasingly used in critically ill patients with respiratory and/or cardiac failure. This study aimed to investigate the epidemiology and risk factors of nosocomial infection (NI) in pediatric patients who underwent ECMO for respiratory and/or circulatory failure. Methods Medical records for patients that were administered underwent ECMO support at Xiangya Second Hospital of Central South University, The Sixth Medical Center of PLA General Hospital, and Children's Hospital Affiliation of Zhengzhou University, from September 2012 to December 2019 were retrospectively reviewed. Clinical data of the patients who developed NI were collected and analyzed. Univariate and multivariate logistic regressions were performed to identify the independent predictive factors of NI during ECMO. Results A total of 54 first episodes of NI were identified in the 190 patients on ECMO, including 32 cases of respiratory tract infections, 20 cases of bloodstream infections, and 2 cases of surgical site wound infections. Gram-negative pathogens were the dominant pathogens isolated, accounting for 92.6% of the NI. The incidence of ECMO-related NI was 47.6 cases per 1,000 ECMO days. In the univariate logistic regression, ECMO mode, ECMO duration, ICU duration, and peritoneal dialysis were associated with the development of NI in patients with ECMO support. However, in the multivariate analysis, only ECMO duration (OR = 2.46, 95%CI: 1.10, 5.51; P = 0.029), ICU duration (OR = 1.35, 95%CI: 1.05, 1.59; P = 0.017) and peritoneal dialysis (OR = 2.69, 95%CI: 1.08, 5.73; P = 0.031) were the independent predictive factors for NI during ECMO support. Conclusion This study identified the significant correlation between ECMO-related NI and ECMO duration, ICU duration, and peritoneal dialysis. Appropriate preventive measures are needed for hospitals to reduce the incidence of ECMO in pediatric patients.